6b-3-7=6b-10

Simple and best practice solution for 6b-3-7=6b-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6b-3-7=6b-10 equation:


Simplifying
6b + -3 + -7 = 6b + -10

Reorder the terms:
-3 + -7 + 6b = 6b + -10

Combine like terms: -3 + -7 = -10
-10 + 6b = 6b + -10

Reorder the terms:
-10 + 6b = -10 + 6b

Add '10' to each side of the equation.
-10 + 10 + 6b = -10 + 10 + 6b

Combine like terms: -10 + 10 = 0
0 + 6b = -10 + 10 + 6b
6b = -10 + 10 + 6b

Combine like terms: -10 + 10 = 0
6b = 0 + 6b
6b = 6b

Add '-6b' to each side of the equation.
6b + -6b = 6b + -6b

Combine like terms: 6b + -6b = 0
0 = 6b + -6b

Combine like terms: 6b + -6b = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 0.09-0.01(x+1)=0.02(2-x) | | 1/6=x/50 | | 2n-q= | | 22/4=55/m | | 5x+5=15x-7-10x | | 5-7X-6X=14-3X | | 2(3)-8= | | 12/w-8=28 | | 9-2[3x+7]=13 | | y^2=x^3-8x | | 5=4-21 | | 5x+5x+x=180 | | 9x+3+3x=30 | | 7+-5x=-5x+-6x+7 | | 7=12n-4 | | -1/5h=11 | | 4x+-5=2x+1 | | -1/18d=-3 | | 8=4/(1-r) | | 12-36-5x=7x | | 1/9g=20 | | 30/1000 | | [x-9]=4 | | 2/x=7/10 | | x-(-10)=99 | | 3=a-7 | | (Y-5)(3y+2)= | | 350+50=40d | | h=-16t^2+4t+48 | | 8x+1=81+2x | | 105x-200=25x+120 | | -3r=42-15 |

Equations solver categories